Towards direct electroanalysis in seawater: understanding the role of the buffer capacity of seawater in proton-coupled electron transfer reactions - Pindar, R; Batchelor-McAuley, C; Yang, M; Compton, R (American Chemical Society, 2021)
The study of electrochemical reactions in seawater requires understanding of the associated coupled chemistry with the components of seawater, especially the role of the carbonate-bicarbonate buffer system in the case of proton coupled electron transfer reactions. We report the comparative paradigmatic voltammetric response of the reversible hydrogen oxidation reaction (HOR) in the absence or presence of dibasic phosphate, formate or bicarbonate. Electrochemically and chemically reversible voltammetry is seen in aqueous 0.7 M NaCl at platinum macro-electrodes in the absence of a buffer whilst the presence of a chemically stable buffer systems, such as phosphate or formate, leads either to a cathodic shift in the oxidation potential for high buffer concentrations or to a split wave for concentrations approximately a factor of two less than the dissolved H2. In the case of bicarbonate buffer the dehydration of carbonic acid on the voltammetric timescale leads to chemically irreversible voltammetric behaviour, with a similar response measured in authentic seawater. Numerical simulations based on a simple Nernstian model with literature values for kinetic and thermodynamic parameters are reported which display excellent agreement with experiment.